2015
DOI: 10.1007/s12306-015-0392-x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of arthroscopic single-bundle anterior cruciate ligament reconstruction: anteromedial portal technique versus transtibial drilling technique

Abstract: There is no superiority of AMP technique on TT technique in ACL reconstructive surgeries. It could be suggested that performing a well-done technique, either TT or AMP, may be more important than only choosing a technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Antero-medial technique has gained more popularity recently due to a more vertical tibial tunnel, less graft tunnel mismatch, greater graft obliquity, centrally placed femoral graft, better pivot shift and rotational stability. 2,10,17 Nevertheless, anteromedial technique includes a risk of blow out of the lateral femoral condyle, articular damage, has a steep learning curve as compared to the trans-tibial technique, short femoral tunnel lengths making the graft passage little tedious. 7,18,19 In the present study, there was a statistically significant difference in both the groups in terms of femoral tunnel position.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antero-medial technique has gained more popularity recently due to a more vertical tibial tunnel, less graft tunnel mismatch, greater graft obliquity, centrally placed femoral graft, better pivot shift and rotational stability. 2,10,17 Nevertheless, anteromedial technique includes a risk of blow out of the lateral femoral condyle, articular damage, has a steep learning curve as compared to the trans-tibial technique, short femoral tunnel lengths making the graft passage little tedious. 7,18,19 In the present study, there was a statistically significant difference in both the groups in terms of femoral tunnel position.…”
Section: Discussionmentioning
confidence: 99%
“…Anterior cruciate ligament (ACL) is one of the main structures of the knee and is responsible for anteroposterior and rotational stabilization in transverse and frontal plane. 1,2 Anterior knee instability associated with rupture of the anterior cruciate ligament is a disabling clinical problem, especially in an athletic individual, it predisposes the knee to subsequent injuries like secondary meniscal tear and chondral injuries. 3 Tunnel position at femur and tibial side and subsequent graft position are of one of the major determinants for a long term successful outcome in ACL injuries.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 However, controversy still remains as some outcome studies and systematic reviews have shown no clinical differences and no difference in failure rates in short-to mid-term follow-up between TT and AMP techniques. 10,11 In our technique (Video 1), a 7-mm over-the-back offset femoral guide is introduced through the AMP and placed over the posterior edge of the femur. The knee is flexed to 120 and the guide pin is assessed to ensure it exits anterolateral and not posteriorly through the femur.…”
Section: Discussionmentioning
confidence: 99%
“…The low AMP was created under arthroscopic visualization; a spinal needle was advanced into the joint just above the anterior horn of the medial meniscus and 1.5 cm medial to the medial border of patellar tendon and to create the femoral tunnel independently from the tibial tunnel. It is important to keep a security distance at least 2 mm from the cartilage of the medial femoral condyle once the drill passes through this portal [ 16 ]. The midpoints of the remnants of the anteromedial and posterolateral bundles of the ACL were marked with a thermal device.…”
Section: Methodsmentioning
confidence: 99%